-v+12=

Simple and best practice solution for -v+12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -v+12= equation:


Simplifying
-1v + 12 = 0

Reorder the terms:
12 + -1v = 0

Solving
12 + -1v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -1v = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -1v = 0 + -12
-1v = 0 + -12

Combine like terms: 0 + -12 = -12
-1v = -12

Divide each side by '-1'.
v = 12

Simplifying
v = 12

See similar equations:

| X^4-18x^2+18=o | | -x^2-2x+1=9 | | x+3+7x-9=82 | | 5(y+-7)+-2y=1+-3[(4y+7)+-2(y+-3)] | | 10r-r= | | 5x^2+26x+32=0 | | 3(4x-2y)+2(x+2y)= | | 2x+11=6x-5-4x | | 11x-3=2x+9 | | 4x/3+2=5 | | -35x+12=28x+19 | | 2x^2+3((-2x+13)/3)^2-35=0 | | A+B+B+B+80+9=100 | | 4=ln(y+4) | | 4x+28x-32=0 | | 4(x-6)-6=x-14 | | 6*3/7*3*1/3/1*2/7 | | 4=Ln(y+1) | | 11/5n=4n+20 | | 6x+8=6x-13 | | -13.00+2.00x= | | ProveA+B+B+B+80+90=100 | | 0.1x+(3x+20)/5=0.5 | | (3x-2y+1)dx+(3x-2y+3)dy=0 | | 4(x-6)-6=4x-14 | | y(4x+y)dx-2(x^2-y)dy=0 | | 3(x+6)-4=6x-2 | | 8p-7p+3=-8 | | 66666666d=4 | | 15/14/2/23 | | 7x+4y=33 | | -5a-3=-7(7+4a) |

Equations solver categories